2020
DOI: 10.1186/s40693-020-00094-9
|View full text |Cite
|
Sign up to set email alerts
|

Morphological variation in two sigmodontine rodents along the mainland and the Fuegian archipelago in Chilean southern Patagonia

Abstract: Background: Analysis of morphological variation in archipelagos has been essential to understand the evolution of terrestrial vertebrates. In particular, these natural scenarios allow to assess morphological changes experienced by insular fauna compared to their mainland counterparts. In mammals, morphological changes of insular forms have been observed in size and shape of body and cranial traits. The southern Patagonia of Chile represents a unique scenario to analyze morphological variation in two of the mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
0
6
0
1
Order By: Relevance
“…The second DFA performed (SM, Fig. S2 ) indicates that this population shows significant levels of cranial distinctiveness (see also Valladares-Gómez et al, 2020 ); as such, its subspecific status can be maintained. This status should be further evaluated by means of the analysis of nuclear genetic variation.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The second DFA performed (SM, Fig. S2 ) indicates that this population shows significant levels of cranial distinctiveness (see also Valladares-Gómez et al, 2020 ); as such, its subspecific status can be maintained. This status should be further evaluated by means of the analysis of nuclear genetic variation.…”
Section: Discussionmentioning
confidence: 93%
“…These have demonstrated that variation of the assessed traits is correlated with environmental characteristics, such as water availability and the latitudinal distribution of populations. A possible island effect (see van der Geer, 2018 ) on the skull morphology of the olive mouse has been suggested by Valladares-Gómez et al (2020) for a restricted area of Chilean Patagonia. In turn, those assessments centered on cranial and external variation, accounted for a wide variability that was the basis for the recognition of A .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…La distinción cariotípica que presenta O. yatesi (2n=54, NF=66) respecto a O. longicaudatus (2n=56, NF=66), anteriormente considerada para respaldar la distinción de O. magellanicus (e.g., Weksler y Bonvicino 2015), es mínima y del tenor del observado en otras especies de Oligoryzomys cromosómicamente variables (ver un resumen de la variación cromosómica de Oligoryzomys en Weksler y Bonvicino 2005). Por otro lado, individuos con morfotipo de O. longicaudatus se distribuyen en Puerto Hambre, la localidad típica de O. magellanicus (Valladares et al 2020); si bien no es posible descartar que dos especies, O. longicaudatus y O. magellanicus, se distribuyan en las inmediaciones de Puerto Hambre, hasta el momento no hay evidencia de la existencia de dos especies en dicha zona. Dado lo anterior, en esta lista se considera a O. yatesi, al igual que a O. magallenicus, como sinónimos de O. longicaudatus.…”
Section: Tribu Oryzomyiniunclassified
“…This environmental variability as well as coastal geometry may impact on the body shape variability in terrestrial (i.e., rodents, Valladares‐Gómez et al. 2020) and marine species with shallow vertical distribution, such as some endemic eelpouts.…”
Section: Introductionmentioning
confidence: 99%